2020
DOI: 10.1101/2020.01.03.893792
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

“Running with cancer”: a qualitative study to evaluate barriers and motivations in running for female oncological patients.

Abstract: AbstractNowadays, it is widely acknowledged that low physical activity levels are associated with an increase in terms of both disease recurrence and mortality in cancer survivors. In this light, deciphering those factors able to hamper or facilitate an active lifestyle is crucial in order to increase patients’ adherence to physical activity. The purpose of this study was to explore barriers and motivations in a sample of female oncological patients, practising running using th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…One of the main barriers described by patients to physical exercise is often lack of time. In relation to this, HIIT allows similar benefits to MICT, but involves less time 65 . In addition to being more time‐effective, it can have cost benefits by decreasing the treatment time of each patient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main barriers described by patients to physical exercise is often lack of time. In relation to this, HIIT allows similar benefits to MICT, but involves less time 65 . In addition to being more time‐effective, it can have cost benefits by decreasing the treatment time of each patient.…”
Section: Discussionmentioning
confidence: 99%
“…Since patients with cancer or cancer survivors are prone to physical inactivity, it is critical to ensure adherence to maintain exercise long enough to achieve benefits in CRF or QoL. Safety is also an important factor of concern to both clinicians and patients themselves 65 . It has been shown to be a safe training since it has little or no adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous studies. [16][17][18]20,24,28 Smith et al 16 reported that patients described physical activity as positive behavior for general health, to manage some treatment-related side effects and other chronic conditions (eg, cardiovascular disease). Older breast cancer survivors mentioned that an active lifestyle help to reduce the stress levels and combat depression.…”
Section: Benefitsmentioning
confidence: 99%
“…Unfortunately, in Italy, the literature on physical activity and cancer is still limited, with no clear data regarding the adherence to a physical activity program. 13 Although several investigations have explored attitude, barriers, motivators, and facilitators able to influence the adoption of physical activity in oncological settings, [14][15][16][17][18][19][20][21][22][23][24] no data on Italian patients are available. In order to fill this gap and to successfully design a future interventional study, we have qualitatively explored those factors influencing the adoption of an active lifestyle in cancer patients visiting the outpatients' facilities at the Oncology Unit in Verona Hospital.…”
Section: Introductionmentioning
confidence: 99%